The Role of the Visual Versus Verbal Modality in Learning Novel Verbs - Maria Luisa Lorusso; Laura Pigazzini; Laura Zampini; Michele Burigo; Martina Caccia; Anna Milani; Massimo Molteni (Children)
Background/Objectives: Verbs are considered to be more abstract than nouns, as they represent actions, states, and events, which are less tangible, more flexible in their meaning and thus less univocally specified. It has been suggested that children acquire abstract concepts based on their linguistic contexts of use, making use of semantic and syntactic cues. By contrast, according to theories of embodied cognition, conceptual knowledge is based on physical and perceptual interaction with the world. The present study investigates whether the verbal and the visual modality produce similar or different results in the processes of construction and reactivation of novel verbs, corresponding to new compositional abstract concepts, in children of different ages. In Experiment 1, the acquisition of the concept was determined based on the quality of verbal explanation; in Experiment 2, participants were asked to decide whether a visual representation fitted the concept or not. Thus, response modality could be either explicit or implicit, and either congruent or incongruent with respect to learning modality. Methods: In Experiment 1, 100 children from grade 1 to 5 were asked to explain the meaning of verbs introduced via verbal or visual instances. In Experiment 2, 15 children aged 8 to 10 had to judge pictures as (not) being examples of previously verbally or visually presented novel verbs. Results: The results of Experiment 1 show more accurate explanations after verbal presentation across all grades. In Experiment 2, verbal presentation was no longer associated with more accurate matching responses, but rather with slower decision times. Conclusions: Modality congruence, explicitness and linguistic (semantic and syntactic) factors were all shown to play a role, which is discussed in a developmental perspective.